Ataques cibernéticos e o risco aos sistemas de produção e serviços: uma análise na perspectiva da gestão da qualidade - Berretta, Fernanda Moreira de Souza (Universidade Federal de São Carlos, 2025)
Industry 4.0 is characterized by the integration of digital technologies into manufacturing processes. Cyber-physical systems (CPS) stand out, combining physical and digital components to create connected, automated, and intelligent production environments. However, these systems are vulnerable to cyberattacks, which can have devastating consequences, ranging from production disruptions to physical damage to facilities and equipment. To mitigate these risks, industries have adopted various practices and protocols; however, the role of quality management systems in the context of cybersecurity has been little explored. Quality management can play a crucial role in preventing and detecting cybersecurity issues faced by Industry 4.0 by ensuring that processes and systems comply with security standards and best practices. This dissertation aims to analyze and indicate how quality management can contribute to the prevention and detection of hacker attacks, highlighting its practices and tools that strengthen cybersecurity systems. To achieve this, the methodological approach of Lakatos' research program was used, based on a literature review. This review was divided into two stages: the first consisted of a descriptive analysis, and the second involved scientific mapping using a technique known as text mining. Additionally, a field study was conducted with experts in the field. The research results indicated that the topic is both emerging and relevant, as quality management enables the mitigation of vulnerabilities in systems connected to cyberattacks. The study suggests that multivariate control charts are among the main statistical techniques recommended for detecting anomalies in hyperconnected systems. Furthermore, the strategic role of quality management systems was highlighted. When integrated with cybersecurity systems, they enhance detection and prevention capabilities, with particular emphasis on the ISO 9000 series standards and Total Quality Management (TQM).
Cyberattacks and the risk to production and service systems – an analysis from the perspective of quality management
Keywords: Ciberataques; Cibersegurança; Sistemas de Gestão da Qualidade; Métodos estatísticos; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO